The top 50 most cited articles on superior capsular reconstruction: a bibliometric analysis - Mallery Zeiman, BS; Lee Beauchamp, BS; Ryan S. Marder, MD; Anthony J. Scillia, MD (JSES Reviews, Reports, and Techniques, 2025)
Background: Bibliometric analysis has been used to quantify and assess a scientific publication and its impact. The purpose of this study was to identify and review the top 50 most cited articles discussing superior capsular reconstruction (SCR). Methods: Scopus database was used to search for publications focusing on SCR. The top 50 most cited articles that met the inclusion criteria were reviewed for year and journal of publication, country of origin, study type, level of evidence, and citation density. Results: The total number of citations from the top 50 articles was 2048 (range, 10-196). The year of publication ranged from 2015 to 2022, with the majority (n = 42) being published from 2018 to 2022. The most common level of evidence rating was level V (21 articles) and the majority (81%) of these articles were surgical technique notes. The second most common level of evidence rating was level IV (16 articles) which were all case series. The articles were written across 16 different countries, most commonly the United States (52%), and published in 16 different journals. Conclusion: Most of the top 50 articles on SCR were technical notes and case series. This demonstrates the need for higher level, comparative, and controlled studies examining SCR techniques, outcomes, and complications in the future.